Development of the “SIMANIS” E-booklet as a Family Planning Decision-Making Tool for Women of Reproductive Age (WRA) - Salsabila Balqis Nur'aini; Rita Yulifah; Lisa Purbawaning Wulandari (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
The height opportunity Pregnancy in Women of Reproductive Age (WRA) can cause teasing birth if no accompanied by planning a good family, though WRA participation in the family planning program is sufficient high, fulfillment need contraception and enhancement interest still become challenges. The lack of use sheet ABPK return by midwife in family planning counseling also strengthen need will be an interesting and easy educational media accessible in a way independent by WRA. Research this aim for develop sheet back to ABPK become e-booklet and testing its feasibility. Research and Development (R&D) method with the ADDIE model, consisting of five stages: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. Subject study covering 22 WRA in the practice area independent midwife “S” Subdistrict Kedungkandang, Malang City, 2 lecturers as expert materials and media, and 1 midwife as expert. Instruments used​ in the form of guide interview, guide FGD (Focus Group Discussion), and questionnaire evaluation product. Data analyzed use approach quantitative and qualitative. Research results produce “SIMANIS” e-booklet (Informasi Metode dan Alat Kontrasepsi Minimalis) designed interesting, using image, language simple, and features voice for make it easier understanding independently by WRA. Validation results show this media is in the "very worthy" category with evaluation expert 93% material, 100% media expert, and trial results group small show that 87% of participants give rating “very worthy”. With Thus, the “SIMANIS” e-booklet is very worthy. used as tool help taking decision family planning in WRA.